1996
DOI: 10.1111/j.1151-2916.1996.tb08584.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bi0.5Na0.5TiO3‐PbTiO3M Dielectric Materials

Abstract: Bi0.5Na0.5TiO3 (BNT) modified with Pb showed an increased and broadened dielectric constant and limited grain growth. Pb also lowered the first transition temperature. The phases of BNT were confirmed to be ferroelectric at room temperature which transformed to antiferroelectric above 220°C. When BNT was doped with 10% Pb, the first transition decreased to 140°C and abruptly disappeared in the composition with 17% Pb. The crystal structure of 17%‐Pb‐doped BNT at room temperature is tetragonal, which differs fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…2, the (310) reflection was a single peak for pure BNT and the line splitting of the (310) reflection became obvious with increasing CT content, indicating that the crystal structure turned into a rhombohedral structure as CT was doped. 19 As shown in Fig. 1, the diffraction peaks shifted toward higher angle as the content of CT increased.…”
Section: Resultsmentioning
confidence: 85%
“…2, the (310) reflection was a single peak for pure BNT and the line splitting of the (310) reflection became obvious with increasing CT content, indicating that the crystal structure turned into a rhombohedral structure as CT was doped. 19 As shown in Fig. 1, the diffraction peaks shifted toward higher angle as the content of CT increased.…”
Section: Resultsmentioning
confidence: 85%
“…There are several inconsistent explanations about T d . Some reports indicated that T d is related to the transition between ferroelectric (FE) and antiferroelectric (AFE) phases because double hysteresis loops were observed above T d [3,7]. However, Park [4] and Suchanicz [5] et al found the intermediate phase as mixture of rhombohedral micro-polar regions and a tetragonal non-polar matrix.…”
Section: Resultsmentioning
confidence: 97%
“…BNT belongs to ABO 3 -type perovskites with rhombohedral symmetry at room temperature. Many modifications on BNT have been performed before it can be practically used as piezoelectric devices, such as additions of PbTiO 3 (PT), BaTiO 3 (BT), SrTiO 3 (ST), Bi 0.5 K 0.5 TiO 3 (BKT), CeO 2 , La 2 O 3 , Dy 2 O 3 , etc [2][3][4][5][6][7][8][9]. Among them, BNT-BT system has good piezoelectric properties because of the existence of a rhombohedral (F α )-tetragonal (F β ) morphotropic phase boundary (MPB) [10].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum of dielectric permittivity [2,3,5,6] appeared around 325-335 • C and its value at a frequency of 10 kHz was 2600 [6]. The dielectric loss increased rapidly above this temperature.…”
Section: Introductionmentioning
confidence: 91%